Up regulation of monocyte chemoattractant protein-1 expression in anti-citrulline antibody and immunoglobulin M rheumatoid factor positive subjects precedes onset of inflammatory response and development of overt rheumatoid arthritis. Issue 1 (1st June 2006) - Rantapää-Dahlqvist, S; Boman, K; Tarkowski, A; Hallmans, G
Abstract : Objective: To analyse the inflammatory mediators, including monocyte chemoattractant protein-1 (MCP-1), in blood samples donated years before onset of rheumatoid arthritis. Previously, it has been shown in these individuals that antibodies against cyclic citrullinated peptide (anti-CCP) detectable years before the onset of symptoms have a high predictive value for development of rheumatoid arthritis. Methods: A nested case–control study was performed: patients with rheumatoid arthritis were identified from among blood donors antedating onset by a median of three years (pre-patients, n = 92); four matched controls were selected randomly for each pre-patient. Plasma were analysed for secretory phospholipase A2 (sPLA2) and MCP-1 using ELISA, for high-sensitivity C reactive protein (hsCRP) using the chemiluminescence method and for interleukin-6 using a sensitive bioassay. Results: When the results were stratified for the presence of anti-CCP antibodies and immunoglobulin M-rheumatoid factor (IgM-RF), only MCP-1 levels were found to be significantly raised in patients with anti-CCP and IgM-RF compared with controls. Conclusion: Levels of MCP-1 were significantly increased in the plasma of patients having anti-CCP antibodies or IgM-RF and who later developed rheumatoid arthritis. These findings indicate up regulation of chemotactic activity for leucocytes before the development of rheumatoid arthritis.